2018
DOI: 10.1111/ijd.14349
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term safety and drug survival of acitretin in psoriasis: a retrospective observational study

Abstract: Background This retrospective observational study aimed to investigate the long‐term safety, drug survival, and factors associated with the survival of acitretin in a real‐world setting. Methods Data of adult patients with psoriasis who attended Siriraj Hospital between 2012 and 2017 and were treated with acitretin were reviewed. Demographic data and clinical courses were recorded. The Kaplan–Meier curve and Cox regression were used to calculate drug survival and the factors associated with drug survival, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
36
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 25 publications
8
36
3
Order By: Relevance
“…Chularojanamontri L et al . showed that low doses of acitretin were not related to significant long‐term liver problems …”
Section: Discussionmentioning
confidence: 99%
“…Chularojanamontri L et al . showed that low doses of acitretin were not related to significant long‐term liver problems …”
Section: Discussionmentioning
confidence: 99%
“…Retinoids are derivatives of vitamin A and bind to nuclear receptors, retinoic acid receptors, and retinoid X receptors, which regulate gene transcription such as IL6 [ 6 ]. Retinoids induce keratinocyte differentiation and reduce epidermal hyperplasia, leading to a slowing of cell reproduction [ 62 ]. Etretinate, which is a second-generation retinoid, is used in Japan, and acitretin, which is an active metabolite of etretinate, has a shorter half-life, and is eliminated more rapidly than etretinate, is used in many countries [ 62 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Retinoids induce keratinocyte differentiation and reduce epidermal hyperplasia, leading to a slowing of cell reproduction [ 62 ]. Etretinate, which is a second-generation retinoid, is used in Japan, and acitretin, which is an active metabolite of etretinate, has a shorter half-life, and is eliminated more rapidly than etretinate, is used in many countries [ 62 ]. The Psoriasis Area Severity Index 75 (PASI75) response to acitretin 25, 35, and 50 mg/day groups at week 12 were 47%, 69%, and 53%, respectively [ 63 ].…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…61,62 Regarding acitretin, serum aminotransferase elevation has been noted, but is usually self-limiting. 63 Psoriasis subtypes Nail psoriasis. From an efficacy perspective, we recommend in psoriasis patients with nail disease the TNF antagonists: infliximab, adalimumab, certolizumab pegol and etanercept; the IL12/23 inhibitor: ustekinumab; the IL23/ p19 inhibitors: guselkumab and risankizumab; the IL17 receptor blocker: brodalumab; the IL17 inhibitors: ixekizumab and secukinumab; and the synthetic drug, apremilast.…”
Section: Clinical Recommendationsmentioning
confidence: 99%